Prognostic value of interim PET/CT in GCB and non-GCB DLBCL: comparison of the Deauville five-point scale and the ΔSUVmax method - Na Sun; Wenli Qiao; Taisong Wang; Yan Xing; Jinhua Zhao (BMC Cancer)
Abstract Background This study aimed to identify the prognostic value of interim 18F-FDG PET/CT (I-PET) for germinal center B-cell-like (GCB) and non-GCB diffuse large B-cell lymphoma (DLBCL), respectively. Methods Baseline 18F-FDG PET/CT (B-PET) and I-PET scans were performed in 112 patients with DLBCL. The prognostic value of I-PET using the Deauville five-point scale (D-5PS) criteria or percentage decrease in SUVmax (∆SUVmax) for GCB and non-GCB DLBCL were evaluated. Results A significant difference in progression-free survival (PFS) was found between GCB and non-GCB DLBCL patients (P < 0.05). Based on D-5PS criteria, I-PET was divided into positive (score > 3) and negative (score ≤ 3) subgroups. Results indicated that I-PET using D-5PS criteria was an independent predictor for PFS of GCB DLBCL (P < 0.05), but not for overall survival (OS) (P > 0.05). For non-GCB DLBCL, PFS and OS were significantly higher in I-PET negative group than I-PET positive group (P < 0.05). Receiver operating characteristic (ROC) curve analysis proved that I-PET using ΔSUVmax can also effectively predict PFS and OS of non-GCB DLBCL (P < 0.05), but not for GCB DLBCL (P > 0.05). Based on the optimal threshold found by ROC curve analysis, patients were dichotomized into ∆SUVmax high and low groups. Log-rank test and Cox regression demonstrated that the layered ∆SUVmax was predictive of PFS and OS in non-GCB DLBCL (P < 0.05). Conclusions I-PET may have different prognostic values for GCB and non-GCB DLBCL. Thus, the pathology type of DLBCL may be considered while using I-PET as a prognostic tool in the future.